BIRC5 is a target for molecular imaging and detection of human pancreatic cancer. (10th August 2019) - Liu, Shi-He; Hong, Yeahwa; Markowiak, Stephen; Sanchez, Robbi; Creeden, Justin; Nemunaitis, John; Kalinoski, Andrea; Willey, James; Erhardt, Paul; Lee, Jason; van Dam, Michael; Brunicardi, F. Charles
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a major cause of cancer mortality with a dismal overall survival rate and an urgent need for detection of minute tumors. Current diagnostic modalities have high sensitivity and specificity for larger tumors, but not for minute PDAC. In this study, we test the feasibility of a precision diagnostic platform for detecting and localizing minute human PDAC in mice. This platform includes: 1) defining BIRC5 as an early PDAC-upregulated gene and utilizing an enhanced BIRC5 super-promoter to drive expression of dual Gaussia luciferase (GLuc) and sr39 thymidine kinase (sr39TK) reporter genes exponentially and specifically in PDAC; 2) utilizing a genetically-engineered AAV2 RGD to ensure targeted delivery of GLuc and sr39TK specifically to PDAC; 3) using serologic GLuc and sr39TK microPET/CT imaging to detect and localize minute human PDAC in mice. The study demonstrates feasibility of a precision diagnostic platform using an integrated technology through a multiple-stage amplification strategy of dual reporter genes to enhance the specificity and sensitivity of detection and localization of minute PDAC tumors and currently undetectable disease. Highlights: Engineering of pancreatic ductal organoids as early PDAC. Identification of BIRC5 as an early biomarker. BIRC5-SP TSTA is potent and highly specific to early PDAC. Engineered AAV2 targets PDAC specifically. GLuc and sr39TK are dual diagnostic reporters.